Thermal conductivity of solid CF₂Cl₂ - Pursky, O.I.; Konstantinov, V.A. (Физика низких температур, 2007)
The thermal conductivity of solid CF₂Cl₂ was measured by the linear-flow method in the temperature range 80–115 K under saturated vapor pressure. Special attention is given to the explanation of the heat transfer process under constant density. The temperature dependence of the isochoric thermal conductivity is analyzed within a model in which heat is transferred by phonons and, above the phonon mobility edge, by «diffusive» modes migrating randomly from site to site.